Relationship between enteric pathogens and acute gastroenteritis disease severity: a prospective cohort study. (April 2019) - Xie, J.; Nettel-Aguirre, A.; Lee, B.E.; Chui, L.; Pang, X.L.; Zhuo, R.; Parsons, B.; Vanderkooi, O.G.; Tarr, P.I.; Ali, S.; Dickinson, J.A.; Hagen, E.; et al.
Abstract: Objectives: To evaluate the relationship between individual bacterial and viral pathogens and disease severity. Methods: Children <18 years with three or more episodes of vomiting and/or diarrhoea were enrolled in two Canadian paediatric emergency departments between December 2014 and August 2016. Specimens were analysed employing molecular panels, and outcome data were collected 14 days after enrolment. The primary outcome was severe disease over the entire illness (symptom onset until 14-day follow-up), quantified employing the Modified Vesikari Scale (MVS) score. The score was additionally analysed in two other time periods: index (symptom onset until enrolment) and follow-up (enrolment until 14-day follow-up). Results: Median participant age was 20.7 (IQR: 11.3, 44.2) months; 47.4% (518/1093) and 73.4% (802/1093) of participants had index and total MVS scores ≥11, respectively. The most commonly identified pathogens were rotavirus (289/1093; 26.4%) and norovirus (258/1093; 23.6%). In multivariable analysis, severe disease over the entire illness was associated with rotavirus (OR = 9.60; 95%CI: 5.69, 16.19), Salmonella (OR = 6.61; 95%CI: 1.50, 29.17), adenovirus (OR = 2.53; 95%CI: 1.62, 3.97), and norovirus (OR = 1.43; 95%CI: 1.01, 2.01). Pathogens associated with severe disease at the index visit were: rotavirus only (OR = 6.13; 95%CI: 4.29, 8.75), Salmonella (OR = 4.59; 95%CI: 1.71, 12.29), adenovirus only (OR = 2.06; 95%CI: 1.41, 3.00), rotavirus plus adenovirus (OR = 3.15; 95%CI: 1.35, 7.37), and norovirus (OR = 0.68; 95%CI: 0.49, 0.94). During the follow-up period, rotavirus (OR = 2.21; 95%CI: 1.50, 3.25) and adenovirus (OR = 2.10; 95%CI: 1.39, 3.18) were associated with severe disease. Conclusions: In children presenting for emergency department care with acute gastroenteritis, pathogens identified were predominantly viruses, and several of which were associated with severe disease. Salmonella was the sole bacterium independently associated with severe disease.